Comprehensive Overview of 473 Cases of COVID-19: Outcome Experiences of a Dedicated Hospital in Dhaka, Bangladesh (Global Journal of Medical Research, 2021)
Aim The study aimed to observe and compare the demographic comorbidities biomarkers in different categories of diagnosed COVID-19 patients admitted to a COVID dedicated tertiary care hospital in the pic time of the pandemic 2020 at Dhaka Bangladesh Methods This retrospective study was conducted from May to September 2020 in 720 bed Holy Family Red Crescent Medical College Hospital Four hundred seventy-three patients included in this study diagnosed by RT-PCR of the nasopharyngeal swab were divided into four groups The mild group includes 254 patients the moderate group has 82 patients 38 patents in the severe group and the critical group who were admitted to ICU 99 patients Demographic data available investigation reports of individual patients obtained from hospital records manually and compared between all four different categories of patients
Keywords: COVID-19; biomarkers; co-morbidities; clinical features; severe; critical; Bangladesh